A novel order reduction procedure for linear time invarient interval systems using SGO algorithm - Anand N, Vijaya; Kumar M, Siva; Rao R, Srinivasa (International Journal of Engineering and Technology, 2018)
In this paper, the authors presented a new algorithm for the reduction of high order linear time interval systems. In the proposed method, the Reduced Order Interval Model (ROIM) denominator and numerator polynomials are determined based on minimization ofobjective function comprising of Integral Squared Error r using Social Group Optimization (SGO). The SGO technique is found to be simple, easy in implementation and provides the optimal solution. Applicability and effectiveness of the proposed method are illustrated through a DC motor speed control system and a typical Seventh order system taken from the literature.